Vibration suppression of curved beams traversed by off-center moving loads. (15th September 2015) - Rostam, M.R.; Javid, F.; Esmailzadeh, E.; Younesian, D.
Abstract: In this study six different vibration control strategies are proposed to suppress both the flexural and torsional vibrations of a curved beam traversed by off-center moving loads. The various vibration control strategies employed are: (i) separate tuned-mass-dampers (TMDs), (ii) linked TMDs with a massless connecting rod, (iii) distributed TMDs system, (iv) linked TMDs with intermediate connection, (v) separate TMDs with intermediate dissipating system, and finally (vi) the nonlinear energy sinks (NESs). The curved beam is modeled using finite element model. An optimal design of TMD system is proposed to suppress the effect of non-symmetrical and side-way motion of vehicles traveling on bridges. The dynamic performance of the proposed vibration control strategies are thoroughly evaluated while subjected to different loading conditions: (a) successive moving loads and (b) broadband random excitation. It is shown that while all the proposed strategies can remarkably suppress both types of the vibration, the fifth strategy is the most effective one that provides the largest value of the bending and torsional vibration reduction in the first loading condition.